DETERMINANTS OF DIVIDEND PAYOUT OF INDONESIAN COMPANIES - Octaviana, Irma; Yulianto, Arief (Management Analysis Journal, 2019)
Dividend policy is a decision about how much earning after tax that will paid as dividend rather than being retained for investment in the company. The data from Indonesia Stock Exchange show that there are still many company that do not pay dividends consistently, whereas dividend policy use as a signal given by the company to outsiders for their performance. This study aims to determine the effect of profitability, leverage, and firm size to dividend policy.The type of this research is a quantitative research by using secondary data. The population in this research are the company that listed in Indonesia Stock Exchange period 2005-2017. The samples used are 43 companies with purposive sampling method. The method of data analysis used is multiple linear regression by using fixed effect model (Least Square Dummy Variable). The research results reveals that leverage and firm size affects significantly on the dividend policy, whereas profitability do not affect significantly on the dividend policy.